2005
DOI: 10.1021/jf0484632
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Citrus Limonoids, Flavonoids, and Coumarins

Abstract: A variety of in vitro models such as beta-carotene-linoleic acid, 1,1-diphenyl-2-picryl hydrazyl (DPPH), superoxide, and hamster low-density lipoprotein (LDL) were used to measure the antioxidant activity of 11 citrus bioactive compounds. The compounds tested included two limonoids, limonin (Lim) and limonin 17-beta-D-glucopyranoside (LG); eight flavonoids, apigenin (Api), scutellarein (Scu), kaempferol (Kae), rutin trihydrate (Rut), neohesperidin (Neh), neoeriocitrin (Nee), naringenin (Ngn), and naringin(Ng);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
214
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 397 publications
(228 citation statements)
references
References 42 publications
8
214
0
6
Order By: Relevance
“…Both mesocarp and endocarp of immature CD fruits were able to inhibit the discolouration of b-carotene with IC 50 values of 0.004 and 0.005 mg/ml, respectively at 60 min of incubation). As previously cited CD peel extract is a rich source of flavonoids that showed antioxidant activity by a different mechanism of action 35 . Both apigenin and hesperetin exhibited mild antioxidant potency.…”
Section: Discussionmentioning
confidence: 94%
“…Both mesocarp and endocarp of immature CD fruits were able to inhibit the discolouration of b-carotene with IC 50 values of 0.004 and 0.005 mg/ml, respectively at 60 min of incubation). As previously cited CD peel extract is a rich source of flavonoids that showed antioxidant activity by a different mechanism of action 35 . Both apigenin and hesperetin exhibited mild antioxidant potency.…”
Section: Discussionmentioning
confidence: 94%
“…NRG has been reported to posses several effects on biological system such as antioxidant (Rice-Evans et al, 1996;Cao et al, 1997), anti-inflammatory (Manthey 2000), anticancer (Goldwasser, 2010), antifibrogenic (Lee et al, 2004) and antiatherogenic (Lee et al, 2001). The beneficial effects on human health are mainly due to their antioxidant activity and ability to chelate metals, to scavenge oxygen free-radical, to inhibit enzymes and to prevent oxidation of low-density lipoproteins (LDL) (Madsen et al, 2000;Yu et al, 2005). Even though NRG possesses a wide range of activities, clinical studies exploring different schedules of administration of this drug have been hampered by its extreme water insolubility and poor bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that bergapten possesses anticarcinogenic, antiproliferative, vasorelaxation and antiallergic effects [5][6][7][8][9]. Moreover, it can enhance bone formation and possibly prevent osteoclastic bone resorption in vitro or in vivo [10,11], suggesting that bergapten may prevent or treat osteoporosis and other bone-destruction diseases.…”
Section: Discussionmentioning
confidence: 99%
“…1), a coumarin found in many medicinal plants, has been used for decades in combination with UV radiation in skin photochemotherapy. It has other biological functions, including anticancer [5,6], antioxidative [7,8] and anti-inflammatory [9] effects. Recently, Tang et al and Zhang et al reported that bergapten stimulates activity of osteoblastlike UMR106 cells and enhances bone morphogenetic protein-2 expression and bone formation via p38 and extracellular signal regulated kinase (ERK)-dependent pathway in osteoblasts of human osteosarcoma cell line (MG-63) and human fetal osteoblast (FOB) cell line [10,11].…”
Section: Introductionmentioning
confidence: 99%